Life satisfaction moderates the impact of daily stressors on well-being and health - Chopik, William J; Rosella, Laura; Helliwell, John; Shiba, Koichiro; Kim, Eric S (Health psychology, 2025)
Higher life satisfaction is associated with reduced risk of age-related morbidities and premature mortality. However, the degree to which life satisfaction moderates the physical and mental health-related outcomes of daily stressors remains understudied. In this study, we evaluated whether higher life satisfaction moderated the association between the experience of daily stressors and reports of positive affect, negative affect, and physical symptoms. We used data from a substudy of the Midlife in the United States Study ( = 2,022; conducted 2004-2009). Participants reported their life satisfaction and daily diary entries on stress, positive/negative affect, and physical symptoms. We used multilevel modeling to assess whether life satisfaction moderated stress-related variations in affect and physical symptoms when participants reported a particularly high number of stressors. Higher life satisfaction was associated with lower negative affect and fewer physical symptoms among participants who reported more frequent stressors (i.e., between-subjects). We did not observe associations with positive affect. Life satisfaction also moderated the impact of stressors within individuals, such that people reported higher negative affect and physical symptoms on days with more stressors but this association was reduced among those higher in life satisfaction. The findings from this study advance our understanding of how life satisfaction might confer benefits for mental and physical health, primarily through moderating the effect of stress on poorer outcomes. We discuss the findings in the context of the mechanisms linking psychological well-being to physical health in the context of stress across the lifespan. (PsycInfo Database Record (c) 2025 APA, all rights reserved).